Atomic-scale friction of black phosphorus from first-principles calculations: Insensitivity of friction under the high-load. (August 2022) - Li, Qiang; Su, Fenghua; Tang, Gongbin; Xu, Xing; Chen, Yanjun; Sun, Jianfang
Abstract: The Amontons-Coulomb law shows that friction is proportional to load, which limits application of materials. Lubricants can, black phosphorus (BP), effectively inhibit the rapid increase of friction under high-load. However, there are fewer researches focusing on the friction mechanism of BP under load. Based on first-principles, bilayer BP as friction interface is approved. The increasing average shear strength is positively correlated and almost negligible for σZ < 20.1 and σZ ≥ 20.1 GPa, respectively, implying high-load friction insensitivity of BP. Comparing to Gr and MoS2, high-load friction insensitivity of BP is remarkable, although its friction performance under zero load is inferior relatively. High-load friction insensitivity of BP is closely related to its negative Poisson's ratio that is observed first-time in friction calculation. This will reduce potential dissipation and friction of BP during high-load sliding, due to interlayer-intralayer electronic reconstruction. The conclusions are of great significance for the design of lubrication and microscale mechanism analysis in engineering application. Graphical Abstract: When σZ ≥ 20.1 GPa, increase of average shear strength for BP is almost negligible, which is closely related to its structure and negative Poisson's ratio. Negative Poisson's ratio (σPoilf ≥21.7 GP) is due to interlayer-intralayer electronic reconstruction of BP under the coordination of the load and sliding, which will reduce potential energy dissipation and friction of BP during the high-load sliding. ga1 Highlights: Bilayer BP as the friction interface maybe more universal for its friction performance. The average shear strength is positively correlated and negligible with load for σZ <20.1 and σZ ≥20.1 GPa, respectively, implying a high-load friction insensitivity of BP. High-load friction insensitivity of BP may be closely related to its Negative Poisson's ratio due to interlayer-intralayer electronic reconstruction.